2017
DOI: 10.3390/md15090275
|View full text |Cite
|
Sign up to set email alerts
|

FVIIa-sTF and Thrombin Inhibitory Activities of Compounds Isolated from Microcystis aeruginosa K-139

Abstract: The rise of bleeding and bleeding complications caused by oral anticoagulant use are serious problems nowadays. Strategies that block the initiation step in blood coagulation involving activated factor VII-tissue factor (fVIIa-TF) have been considered. This study explores toxic Microcystis aeruginosa K-139, from Lake Kasumigaura, Ibaraki, Japan, as a promising cyanobacterium for isolation of fVIIa-sTF inhibitors. M. aeruginosa K-139 underwent reversed-phase solid-phase extraction (ODS-SPE) from 20% MeOH to MeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…This value was inferior than that encountered for Micropeptin K139, a serine protease also detected in cyanobacteria. In contrast, microviridins D-F do not affect thrombin activity, most likely due to the absence of an indole motif, which is encountered in microviridin B, suggesting its role as a recognition motif for thrombin [86].…”
Section: Application Of Microviridinsmentioning
confidence: 89%
“…This value was inferior than that encountered for Micropeptin K139, a serine protease also detected in cyanobacteria. In contrast, microviridins D-F do not affect thrombin activity, most likely due to the absence of an indole motif, which is encountered in microviridin B, suggesting its role as a recognition motif for thrombin [86].…”
Section: Application Of Microviridinsmentioning
confidence: 89%
“…This finding adds a new derivative, 4,5-didehydroaraginal (Ddha), to the known building blocks of trypsin-type serine protease inhibiting aeruginosins; others are agmatine, araginol, araginal, 3-aminoethyl-1- N -amidino-Δ 3 -pyrroline [ 3 ] and 1-amidino-2-aminopyrrolidine (Aap) [ 12 ]. A recent study showed that aeruginosin K-139, an araginal containing aeruginosin, blocks the formation of the activated factor VII-soluble Tissue Factor complex (fVIIa-sTF, EC 50 ~166 µM) and inhibits thrombin catalytic activity (EC 50 of 0.66 µM) [ 29 ]. It will be interesting to compare the fVIIa-sTF activity of aeruginosin TR642 with that of aeruginosin K-139 in view of the opposite absolute configuration of the Ile/Leu and Choi sub-units and Ddha versus araginal, respectively.…”
Section: Resultsmentioning
confidence: 99%